Two-Year Outcomes of Visian Implantable Collamer Lens with a Central Hole for Correcting High Myopia - Zhipeng Yan; Huamao Miao; Feng Zhao; Xiaoying Wang; Xun Chen; Meiyan Li; Xingtao Zhou (Journal of Ophthalmology)
Purpose. To investigate two-year outcomes of Visian Implantable Collamer Lens with a central hole (ICL V4c) implantation for correcting high myopia. Methods. Sixty-one eyes of 32 patients went through ICL V4c implantation. Safety, efficacy, predictability, and intraocular pressure were evaluated 2 years postoperatively. Anterior chamber volume (ACV), anterior chamber depth (ACD), anterior chamber angle width (ACAW), and vault were measured using a Scheimpflug tomography imaging system. Results. At 2 years, the spherical equivalent refraction decreased from preoperative −14.62 ± 4.29 D to −0.90 ± 0.95 D, with 79% of the eyes within ±0.50 D and 98% within ±1.00 D of the intended correction. The efficacy index was 1.03 ± 0.23, and the safety index was 1.24 ± 0.26. Corrected distance visual acuity (CDVA) remained unchanged in 23% of the eyes, 75% gained one or more lines of CDVA, and 2% lost one line. The ACV, ACD, and ACAW, respectively, decreased from 193.28 ± 29.15 mm3, 3.15 ± 0.23 mm, and 36.51 ± 6.54 degree to 112.48 ± 17.01 mm3, 2.99 ± 0.23 mm, and 22.54 ± 5.27 degree (p=0.0008,  0.008,  and  0.0003, resp.). Intraocular pressure was 15.39 ± 2.88 mmHg before surgery and was 15.86 ± 4.11 mmHg at 2 years (p=0.11). Conclusion. Implantation of ICL V4c is a safe, effective, and predictable procedure for correcting high myopia. Reduction of anterior chamber space after surgery did not induce intraocular pressure increase during the 2-year follow-up.